2015
DOI: 10.1108/rpj-11-2012-0111
|View full text |Cite
|
Sign up to set email alerts
|

Environmental, health, and safety issues in rapid prototyping

Abstract: Purpose – This study aims to investigate the potential impacts of rapid prototyping systems on the health and safety of operators and the environment, a growing concern given its wide-spread use in industry and academia. Design/methodology/approach – Materials, processing and equipment features were used to identify potential health and safety risks and hazards, as well as environmental effects. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…While Deak (, ) was among the first to address the importance of a health and safety plan of action (e.g., adequate working space, proper air ventilation, proper dust collection, and use of protective gloves and safety glasses) as well as plan of follow up (e.g., written procedures), the impact of AM processes on the health and safety of operators and the environment has been investigated more in detail by Short and colleagues (). The authors provided a “best practices” guide for rapid prototyping laboratories.…”
Section: Health and Safety Issues Related To Additive Manufacturingmentioning
confidence: 99%
“…While Deak (, ) was among the first to address the importance of a health and safety plan of action (e.g., adequate working space, proper air ventilation, proper dust collection, and use of protective gloves and safety glasses) as well as plan of follow up (e.g., written procedures), the impact of AM processes on the health and safety of operators and the environment has been investigated more in detail by Short and colleagues (). The authors provided a “best practices” guide for rapid prototyping laboratories.…”
Section: Health and Safety Issues Related To Additive Manufacturingmentioning
confidence: 99%
“…With increased use of desktop and small-scale 3-D printers in non-industrial settings comes the concern for user health and safety. [2] …”
Section: Introductionmentioning
confidence: 99%
“…Some VOCs are respiratory and mucous membrane irritants [2,6] or allergic asthmagens. [7,8] Ozone is a lung irritant and a reactive gas that may alter indoor air chemistry by interacting with unsaturated VOCs to form secondary organic aerosols and reactive products such as carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different perspectives, energy consumption of AM is considered as the top‐driving factor that needs more academic studies, which is also identified as one of the unsolved issues for AM processes (Drizo and Pegna ; Short et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, attributed to the growing public concerns in climate change, more attention has been drawn to environmental sustainability related performance of AM processes considering energy, ecological, economic, and other aspects (Burkhart and Aurich 2015). Among the different perspectives, energy consumption of AM is considered as the top-driving factor that needs more academic studies, which is also identified as one of the unsolved issues for AM processes (Drizo and Pegna 2006;Short et al 2015).…”
Section: Introductionmentioning
confidence: 99%